O coordenador pedagógico e a carta de intenções: do planejamento à ação - Barreto, Doselene Carvalho de Oliveira (2020)
This research aimed at investigating how pedagogical coordinators of the public educational system of the city of São Paulo, working in CEIs (Centros de Educação Infantil – Children Education Centers) and EMEIs (Escolas Municipais de Educação Infantil – Children Education Municipal Schools), elaborate their Letters of Intentions and which are their teacher training objectives. Our specific objectives were: a) Analyze if and how the school training demands are exposed within the coordinators’ Letters of Intentions; b) Identify if the coordinators introduce problematization and teacher practice articulation proposals that could contribute to break away from practices that are incoherent with childhood pedagogy; c) Analyze the coordinators’ conceptions of childhood and curriculum, which are present in their Letters of Intentions; d) Analyze the coordinators’ pedagogical and political proposals, which are present in their Letters of Intentions; e) Investigate how coordinators elaborate training proposals for the school unit, considering context analysis and teachers’ training needs evaluation. Research approach is qualitative (LÜDKE; ANDRÉ, 1986) and data was produced through Conversation Circle (WARSCHAUER, 2017) and analysis of eight Letters of Intentions, which is the document established by Normative Instruction nº02/19, on Children Education Registers (SECRETARIA MUNICIPAL DE EDUCAÇÃO/COPED, 2019). Theoretical references were based on research by Placco; Almeida; Almeida e Placco; Almeida, Placco e Souza; Formosinho; Imbernón; Souza; Tardif, amongst others, and verse on these professionals’ constituted knowledges, presented in their Letters of Intentions and in their speech during Conversation Circle. Analysis allowed us to understand, through the Letters, that the pedagogical coordinators expose their training intentions by using the Currículo da Cidade: Educação Infantil – Curriculum of the City: Children Education (SME/COPED, 2019) and establish relationships with the theory it implies. In training spaces, the coordinators consider articulation with the teachers’ practices and evaluate their groups’ training through context analysis, even if these proposals are explicit in their Letters. Data analysis showed that it is necessary to invest in training spaces where knowledges articulation and the experience of elaborating training intentions, explicit in their Letters of Intentions, could advance into the elaboration of an action plan aiming at building strategies that could improve their intentions, create conditions to deal with daily routines and provide the constitution of their professionalism